Influence Of Organizational Climate on OCB and Employee Engagement - Wardono, Gadang; Moeins, Anoesyirwan; Sunaryo, Widodo (Riviera Publishing, 2022)
Every industry always wants to be successful and help improve the welfare of its employees, including the cement industry in Bogor Regency. However, not all companies can continue to thrive because of the different organizational climates. This difference is due to differences in the system or way of managing the company itself so that the levels of Organizational Citizenship Behavior (OCB) and Employee engagement are also different. In fact, these two things have a strong influence on increasing the success of a company. This is because, OCB and employee engagement are related to the quality of human resources in each company. For this reason, researchers want to find out more about the effect of Organizational Climate on OCB and Employee Engagement with a case study on the cement industry in Bogor Regency. This research was conducted using an empirical study method using path analysis techniques and Focus Group Discussion (FGD) with 40 respondents. The results of this study are that there is a positive influence between Organizational Climate on OCB and Employee Engagement.